2019
DOI: 10.1126/sciadv.aav5168
|View full text |Cite
|
Sign up to set email alerts
|

Intensified vegetation water use under acid deposition

Abstract: Despite the important role vegetation plays in the global water cycle, the exact controls of vegetation water use, especially the role of soil biogeochemistry, remain elusive. In this study, we reveal a new mechanism of soil biogeochemical control of large-scale vegetation water use. Nitrate and sulfate deposition from fossil fuel burning have caused substantial soil acidification, leading to the leaching of soil base cations. Of these, calcium has a unique role in plant cells by regulating stomatal aperture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
(57 reference statements)
1
24
1
Order By: Relevance
“…Our results are in line with a prior meta-analysis, which reported a negative relationship between the response of ecosystem aboveground net primary productivity and soil pH (Tian, Wang, et al, 2016). In this study, we also found a negative relationship between the response of leaf transpiration rate and soil pH (Figure 8p), possibly owing to greater reduction in Ca 2+ under lower pH, which can intensify plant water use (Lanning et al, 2019;McLaughlin & Wimmer, 1999).…”
Section: Environmental Moderatorssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with a prior meta-analysis, which reported a negative relationship between the response of ecosystem aboveground net primary productivity and soil pH (Tian, Wang, et al, 2016). In this study, we also found a negative relationship between the response of leaf transpiration rate and soil pH (Figure 8p), possibly owing to greater reduction in Ca 2+ under lower pH, which can intensify plant water use (Lanning et al, 2019;McLaughlin & Wimmer, 1999).…”
Section: Environmental Moderatorssupporting
confidence: 92%
“…First, N addition would intensify soil acidification, leading to leaching of base cations (e.g., Ca 2+ , K + , and Mg 2+ ; Lucas et al, 2011; Tian & Niu, 2015). Then, reduction in Ca 2+ can affect the regulation of stomatal aperture, preventing stomatal closure and sustaining the transpiration, and thus intensifying plant water use (Lanning et al, 2019). Taken together, our results indicate that the positive effects of N addition on plant photosynthetic C gain might not be lasting in the long term, while the positive effects on plant water consumption seem to become greater if increased levels of N addition persist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to greater moisture availability, changing soil biogeochemistry may be partially responsible for rising Δ 13 C (1976-2010), as Ca 2+ deficit prevented stomatal closure and, thus, sustained transpiration. Based on results from a long-term, watershed acidification experiment, Lanning et al (2019) suggested that Ca 2+ leaching altered tree stomatal response and vegetation water use, causing an increase in transpiration that depleted available soil water, as measured at the watershed scale. Examining the regional hydrological cycle in the north-eastern USA (1960-2012), Vadeboncoeur et al (2018) highlighted higher ET in northern watersheds compared with southern ones (i.e.…”
Section: Acid Deposition Stomatal Response and Vegetation Water Usementioning
confidence: 99%
“…These results on one hand suggest that variations in S dep outweigh changes in N dep and c a . S dep may influence tree water-use directly, by affecting g s 22 or indirectly, by leading to soil acidification, loss of calcium, which play a significant role in controlling g s 39 . On the other hand, they indicate that it is essential to account for changes caused by stand development and management history, if the goal is to disentangle climatic and anthropogenic drivers of change in iWUE.…”
mentioning
confidence: 99%